Creating Millennial Generation Loyalty Through Customer Perceived Value on Halal Local Cosmetic Products - Immawati, Siti Asriah; Jumarno, Jumarno; Kasmo, Arief Bowo Prayoga; Tafiprios, Tafiprios (Universitas Muhammadiyah Sorong, 2024)
With the rapid growth of Indonesia's cosmetics industry, the cosmetic industry has the opportunity to compete by making halal labelled products. The aim of this research is to find out how the value the customer considers affects customer loyalty by looking at how satisfied local millennials are with halal cosmetics. This research involves 250 millennials living in Jabodetabek. Using Smart-PLS, data is collected through questionnaires distributed through Google Forms. The results of the analysis show that the value perceived by the customer has a positive and significant impact on the consumer loyalty, the value experienced by the client has a negative and significant effect on consumer satisfaction, and the satisfaction of consumers has a significant and positive effect on the customer loyalty and the average consumer’s satisfaction.